О нахождении трематоды Cotylotretus cubanicus у диких водоплавающих птиц - Звержановский, М.И. (Вестник зоологии, 1976)
First in the territory of the USSR Cotylotretus cubanicus A r t j u c h was found in Anas platyrhyncha L. and Aythya nyroca L. The development cycle of this trematode is not studied.